Pengaruh ukuran perusahaan, leverage dan modal kerja terhadap nilai perusahaan - Syahzuni, Barlia Annis; Edwani, Vellin Meilandari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Maximizing the value of the company is important for a company, because that means maximizing shareholder wealth which is in line with the company's main goals. The purpose of this study was to determine the effect of company size, Leverage and working capital on firm value in the basic materials industry sector from 2017 to 2021. The data source comes from the annual financial statements of companies listed on the IDX with a sampling technique using the appropriate purposive sampling method. with research criteria. The research period was taken for 5 years from 2017 to 2021 with a total sample data used of 60 data from 12 companies. The results of this study show that simultaneously firm size, Leverage and working capital have a significant effect on firm value. Partially, firm size, Leverage and working capital also have a significant effect on firm value.